2012 Oceans 2012
DOI: 10.1109/oceans.2012.6404894
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal sensor networks for more effective sensing in Irish coastal and freshwater environments

Abstract: Abstract-The world's oceans represent a vital resource to global economies and there exists huge economic opportunity that remains unexploited. However along with this huge potential there rests a responsibility into understanding the effects various developments may have on our natural ecosystem. This along with a variety of other issues necessitates a need for continuous and reliable monitoring of the marine and freshwater environment. The potential for innovative technology development for marine and freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…It can be found that most of the efforts are related to general ocean sensing and monitoring [ 4 , 23 , 40 , 44 , 46 , 47 , 50 , 53 , 55 – 57 ] and water quality monitoring [ 39 , 42 , 43 , 49 , 51 , 54 , 58 ]. Some specific efforts have been made for fish farm monitoring [ 45 , 48 ], coral reef monitoring [ 41 ], and marine shellfish monitoring [ 52 ].…”
Section: State-of-the-art Reviewmentioning
confidence: 99%
“…It can be found that most of the efforts are related to general ocean sensing and monitoring [ 4 , 23 , 40 , 44 , 46 , 47 , 50 , 53 , 55 – 57 ] and water quality monitoring [ 39 , 42 , 43 , 49 , 51 , 54 , 58 ]. Some specific efforts have been made for fish farm monitoring [ 45 , 48 ], coral reef monitoring [ 41 ], and marine shellfish monitoring [ 52 ].…”
Section: State-of-the-art Reviewmentioning
confidence: 99%
“…There have been several implementations of WSN-based WQM systems that have been tested or deployed in Australia [Silva et al 2011;Rao et al 2013], China [Jiang et al 2009;Jin et al 2010 [Wiranto et al 2015], Ireland [O'Flyrm et al 2007;Regan et al 2009;O'Connor et al 2012;Garcia et al 2012;Murphy et al 2015], Malawi [Zennaro et al 2009], Malaysia [Rasin and Abdullah 2009], Mexico [Curiel et al 2016], Peru [Ritter et al 2014], Portugal [Postolache et al 2014], Tanzania [Faustine et al 2014], Turkey [Tuna et al 2014], and the United States [Yang et al 2002;Seders et al 2007;Burke and Allenby 2014;Sun et al 2016]. Details of these systems are summarized in Tables VIII and IX. In addition to these implementations, researchers in China [Yang and Pan 2010;Chen et al 2011], India [Verma and Prachi 2012], the kingdom of Saudi Arabia [Aleisa 2013], and Zambia [Chaamwe 2010] describe the limitations of the current WQM practice adopted in their region, and they propose the idea and present the benefit of automating WQM through the adoption of WSN technologies.…”
Section: Implementations Of Wsn-based Wqm Systemsmentioning
confidence: 99%
“…These different implementations agree on a general WSN-based WQM framework, which includes the use of WSNs, a local monitoring station (or BS), and a remote monitoring station, as described is Section 5.1. However, most of the existing solutions only focus on the design and implementation of the local monitoring network (i.e., a WSN and local monitoring station), either through laboratory feasibility testing [Chaamwe 2010;Wang et al 2011;Chen et al 2011] or field deployment [Seders et al 2007; O'Flyrm et al 2007;Sun et al 2016], and some of the references actually include the final interconnection with the remote monitoring station [Yang and Pan 2010;Silva et al 2011;Alkandari et al 2011;O'Connor et al 2012;Faustine et al 2014]. Several works provide automated warning signals displayed on computer screens or communicated to decision makers via text or email.…”
Section: Implementations Of Wsn-based Wqm Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre los retos que mencionan se tienen un mejor nivel de resistencia al agua; generar nodos más robustos debido a lo agresivo del entorno marino; el más alto consumo de energía debido a las grandes distancias de cobertura y su alta movilidad causado por las corrientes marinas, además de que los nodos se enfrentan al problema de líneas de vista más inestables. Otros trabajos han enfocado su esfuerzo en el monitoreo de los océanos en general [16][17] y el monitoreo de la calidad del agua [18][19]. Otros se han dirigido al monitoreo de granjas de peces [20] así como el monitoreo de arrecifes de coral [21] y el monitoreo de tortugas marinas [22].…”
Section: Trabajos Relacionadosunclassified